Business, grammar & practice. - Duckworth, Michael, ....- (Oxford : University Press, 2003)
Description A grammar reference guide for professional adults, now revised and updated. How can it be used? - In the classroom. - For homework. - For self-study. Who is it for? - For both job-experienced and pre-experience students who want to improve their grammar. Key features - Detailed explanations of the key grammar areas, illustrated by contextualized examples. - Practice activities focusing on accuracy and based on language contexts relevant to the professional adult learner. - Authentic source material, which will encourage learners to develop and expand their business vocabulary as well as grammatical competence. - End-of-section progress tests.
Keywords: Correspondentie -- Engels; Engels -- Taalgebruik